Evaluating monetary policy - Lars E.O. Svensson (Sveriges Riksbank, 2009)
Evaluating inflation-targeting monetary policy is more complicated than checking whether inflation has been on target, because inflation control is imperfect and flexible inflation targeting means that deviations from target may be deliberate in order to stabilize the real economy. A modified Taylor curve, the forecast Taylor curve, showing the tradeoff between the variability of the inflation-gap and output-gap forecasts can be used to evaluate policy ex ante, that is, taking into account the information available at the time of the policy decisions, and even evaluate policy in real time. In particular, by plotting mean squared gaps of inflation and output-gap forecasts for alternative policy-rate paths, it may be examined whether policy has achieved an efficient stabilization of both inflation and the real economy and what relative weight on the stability of inflation and the real economy has effectively been applied. Ex ante evaluation may be more relevant than evaluation ex post, after the fact. Publication of the interest-rate path also allows the evaluation of its credibility and the effectiveness of the implementation of monetary policy.
Keywords: 330; Geldpolitik; Inflationssteuerung; Taylor-Regel; Gesamtwirtschaftliche Produktion; Zentralbank; Wirtschaftsprognose